Asociación entre el diámetro y altura comercial en el crecimiento de las plantas de Guatteria elata R. E. Fr. en diferentes muestras en bosque natural. Puerto Almendra, Loreto, Perú – 2022 - Huaman Andoa, Shantal Ramesh (2024)
The research was carried out in Puerto Almendra, belonging to the Loreto region. OBJECTIVE: determine the degree of relationship between the diameter and commercial height of Guatteria elata R. E. Fr. “carahuasca” plants in different samples in natural forest. METHODOLOGY: Trees with DBH ≥ 10 cm were used and 40 individuals were recorded in total, forming 4 samples, the first had 6 diameter classes, the second had 8 diameter classes, the third had 30 individuals chosen at random and the representative sample – sample 4 was 16 individuals. RESULTS: the cubic allometric model is the one that best fits the commercial diameter-height association in G. elata R. E. Fr. plants with a degree of association between Good and Excellent. CONCLUSION: the prediction equation chosen was from sample 2: ŷ = 1.710 + (0.169 x t) + (0,040 x t2) + (-0,001 x t3).